(untitled) (ACUMEN: INTERNATIONAL JOURNAL OF MULTIDISCIPLINARY RESEARCH, 2024)
This article explores the importance of English in understanding assets and liabilities in financial statements. Details are provided on how assets and liabilities are defined and classified in a financial content. The article also examines the importance of using clear language in financial statements, examples of language misunderstandings and best practices for clearly expressing financial concepts. The role of English as a global business language is also highlighted, helping to make financial information easier to understand for multilingual audiences. In conclusion, the article highlights the importance of clear and transparent communication in financial reporting, which builds trust among all stakeholders.